2020
DOI: 10.4081/ijfs.2020.8463
|View full text |Cite
|
Sign up to set email alerts
|

Geographical restriction of Hepatitis E virus circulation in wild boars (Sus scrofa) in Emilia-Romagna region, Northern Italy

Abstract: Hepatitis E virus (HEV) is a singlestrand RNA virus that causes an acute viral hepatitis in humans. Among its eight recognized genotypes, HEV-3 and HEV-4 are zoonotic, infecting humans, pigs and wild boars. Recently, HEV-3 has been also detected in red deer, which represents another reservoir of HEV. Consumption of raw pork products (mainly liver sausages), undercooked wild boar meat, raw wild boar liver and deer meat has been responsible for foodborne HEV human worldwide. From November 2018 to March 2019, liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
4
6
1
Order By: Relevance
“…Conversely to our results (62.5% 5/8 positive livers belonged to adult animals and 37.5% 3/8 pre-puberal/puberal subjects), Di Pasquale et al (2019) found specular positivity rates: 55.5% (30/54 positive animals) in juveniles, 29.6% (16/54) in sub adults (classified as pre/puberal subjects), and 14.9% (8/54) in adults. Similar data reported by Di Pasquale et al (2019), were also observed by other research groups (Martinelli et al, 2015;Bonardi et al, 2020). These differences can be explained by sample collection; indeed, in the hunting season reported in our study, prepuberal/puberal and adult subjects were mostly collected, whereas nonjuvenile animal was included in the sampling.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Conversely to our results (62.5% 5/8 positive livers belonged to adult animals and 37.5% 3/8 pre-puberal/puberal subjects), Di Pasquale et al (2019) found specular positivity rates: 55.5% (30/54 positive animals) in juveniles, 29.6% (16/54) in sub adults (classified as pre/puberal subjects), and 14.9% (8/54) in adults. Similar data reported by Di Pasquale et al (2019), were also observed by other research groups (Martinelli et al, 2015;Bonardi et al, 2020). These differences can be explained by sample collection; indeed, in the hunting season reported in our study, prepuberal/puberal and adult subjects were mostly collected, whereas nonjuvenile animal was included in the sampling.…”
Section: Discussionsupporting
confidence: 90%
“…5.12% (5.12% -95% CI: 1.6-8.4%) liver samples presented HEV RNA similarly to the value 3.7% (HEV 3e and 3f), 1.9% (HEV 3e, c, f), and 1.2% (HEV 3f) reported in Toscana (Caruso et al, 2015), in Liguria (Serracca et al, 2015), and Lombardy (Sondrio province) (Arnaboldi et al, 2021) regions, respectively. On the other hand, our results were lower than 31.5% and 23.8% (HEV 3a) in Emilia-Romagna (Parma province) (Bonardi et al, 2020;Arnaboldi et al, 2021), 13.7% (HEV 3c) in Abruzzo region (Aprea et al, 2018;Lo Presti et al, 2020), and 16.3% (HEV 3a, c, f, and l) in Lazio region (Di Pasquale et al, 2019).…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…In this study, both the prevalence of roe deer and the viral load in the liver tissue of infected subjects were not lower than those highlighted in previous studies on wild boars in the same area [ 9 , 28 , 52 ]. Furthermore, a recent paper suggests that the presence of deer populations is itself a risk factor for the spread of HEV infection in various wild boar populations [ 53 ]. All these elements are strongly indicative that cervids are not only dead-end hosts, but that they could contribute to keeping the hepatitis E virus in a specific territory, as well as representing a documented foodborne source of transmission for the man [ 12 , 54 ].…”
Section: Discussionmentioning
confidence: 99%